Bearing characteristics and settlement calculation method of pile groups in beaded karst areas - Jie Li; Jiaxing Tao; Juncheng He; Jianhui He; Mingquan Huang; Yan Zhao; Mingjie Zhou (PLoS ONE, 2025)
In order to explore the influence of the different position of karst on the bearing capacity of pile group foundation, a theoretical analysis was carried out from the perspective of the reduction rate of pile group effect. Combined with the calculation method of pile foundation settlement, the calculation formula for pile group foundation settlement corresponding to different relative position conditions of karst caves was derived. Finite element numerical simulations were conducted using data from real pile foundation projects, and the results were verified with field measurements. The results demonstrate that the proposed method for analyzing pile bearing characteristics is widely applicable. When the karst cave is located beneath the central area of the pile foundation, the ultimate bearing capacity is relatively high. However, when the karst cave is located in the peripheral area, the ultimate bearing capacity decreases. The conclusions provide a theoretical basis and practical guidance for managing and controlling similar engineering problems.